PUREZA E MORALIDADE EVANGÉLICA: UM ESTUDO DO DISCURSO EVANGÉLICO BRASILEIRO SOBRE A SEXUALIDADE - Rodrigues, Silvia Geruza Fernandes (2011)
This dissertation intends to analyze different speeches about sexuality in five Brazilian protestant leaders to observe in which basis they sustain their teachings and statements to control and rule the Christians sexual behavior. Trough the study of the historical and social development of Christianity and its relationship with sexuality since the second century A.D. to the present Day, this research intends to perceive how Hellenic dualism and Neo-Platonism were able to pervade the sexuality concepts from the Early Fathers to the present time. The criteria used to those the protestant leaders were their written texts. Jaime Kemp, North American missionary, writer and speaker to the youth and couples in churches and Congresses; Robinson Cavalcanti, Episcopalian Anglican Bishop, writer and speaker in important national conferences; Paulo César e Claudete Brito, pastors in the city of Rio de Janeiro; Carlos Eduardo Calvani, Anglican priest, conference speaker and a writer. Calvani outstands as a dissonant voice when dealing with the theme of sexuality. This research intends to contrast the two views of the Christian sexual moral: the essentialist and the personalist, while conversing with some catholic moral theologians to interrelate sexuality with psychology, anthropology, Human and Social Sciences so sexuality is perceived in its human and subjective dimension.